Employing customizable digital observation tools to support classroom-focused pedagogical partnership - Donahoe, Emily; Staggs, Jessica; Vargas, Dominique (International Journal for Students as Partners, 2023)
This case study examines the use of the Generalized Observation and Reflection Platform (GORP)—a digital tool for developing fully customizable observation protocols as well as for collecting, analyzing, and reporting quantitative observation data—within the University of Notre Dame’s Inclusive Pedagogy Partnership. We found that the tool enhanced collaboration between partners in articulating and setting goals for their work and in highlighting and conceptualizing growth in the classroom. It also improved the efficiency of classroom observations and generated visual and quantitative data that usefully supplemented more traditional qualitative observations. Because of a steep learning curve, however, providing extensive time and support for partners in incorporating GORP was key to its successful implementation. We also suggest that GORP may serve as a useful tool for helping partners move between product- and process-oriented understandings of their work and for empowering student partners to take ownership of their observations.